REMOTE TECHNOLOGY FOR THE DEVELOPMENT OF PRACTICAL SKILLS - Besik Ch. Meskhi; Larisa E. Pustovaya; Ekaterina M. Bayan; Anna D. Pustovaya; Maria G. Zharkova (Высшее образование в России)
Abstract. The paper presents the experience of using the distance forms of education in training of engineering specialties students. The influence of multimedia files as a part of the structure of electronic resource «Ecological monitoring», which is based on Moodle platform, on the degree of mastering of professional competencies was studied. The existence of such element allows students to look through certain parts of lectures repeatedly, which are individually necessary for lasting assimilation of educational and practical material and its subsequent reproduction. It assists to create an individual learning path and to optimize the dialogue with a pedagogue, which is especially important for students with disabilities. We established by methods of survey and statistical analysis of dynamics of passing the final certification on the discipline that the introduction of media files in electronic courses has a significant impact on the rate and degree of mastering practical skills, attendance of classes and assists to increase interest in the studied discipline and, as a consequence the performance as a whole.